SnO2-coated In2O3 visible light excitation gas-sensitive material as well as preparation method and application thereof

By designing SnO2@In2O3 visible light excitation gas-sensitive material, the existing NO2 gas sensors have been solved for working difficulties at room temperature, and fast response and high sensitivity NO2 gas detection have been achieved. The response recovery time has been significantly shortened and the detection lower limit has been greatly improved.

CN119780170APending Publication Date: 2025-04-08DALIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510036344.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing SnO2-based NO2 gas sensors have problems such as high working temperature and long response recovery time, making it difficult to achieve high sensitivity and high stability detection in a normal temperature environment.

Method used

A SnO2@In2O3 visible light excitation gas-sensitive material was designed, and SnO2 hollow nanospheres and In2O3 hollow microtubules were synthesized by a one-step hydrothermal method, and the material was prepared by mixing and heating in a certain proportion. The In:Sn atomic ratio is 20~60at%, to achieve fast response and short response recovery time.

Benefits of technology

Under room temperature, SnO2@In2O3 visible light excitation gas-sensitive material achieves rapid response and high sensitivity detection to NO2 gas, shortening the response recovery time to within 30s, the detection lower limit reaches 100 ppb, and has good repeatability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119780170A_ABST
    Figure CN119780170A_ABST
Patent Text Reader

Abstract

The invention particularly relates to a SnO2-coated In2O3 visible light excitation gas-sensitive material as well as a preparation method and application thereof. In order to solve the technical problems that a SnO2-based NO2 gas sensor is relatively high in working temperature and relatively long in response recovery time in the prior art, the invention provides the SnO2-coated In2O3 visible light excitation gas-sensitive material which is a eutectic material prepared by grinding and heating SnO2 hollow nanospheres and In2O3 hollow microtubes according to an In: Sn atomic ratio of 20-60 at%, and the SnO2-coated In2O3 visible light excitation gas-sensitive material is a SnO2-coated In2O3 visible light excitation gas-sensitive material. After light is added, a large number of photo-generated electrons and photo-generated holes are formed to participate in the reaction, and sensitive and stable detection on nitrogen dioxide under the room temperature condition can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nitrogen dioxide detection, and in particular to a SnO2@In2O3 visible light excited gas sensitive material, a preparation method of the material and application in the field of nitrogen dioxide detection. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] With the rapid development of global urbanization, industrialization and automobile industry, various harmful gases are emitted. Nitrogen dioxide (NO2) is one of the main air pollutants, which can react with water and oxygen in the atmosphere to produce acid rain or photochemical smog, seriously threatening the safety of life on earth. The World Health Organization (WHO) has set a short-term exposure threshold (TLV) of 0.5ppm of NO2 in the atmosphere. Long-term exposure to the atmosphere may also cause eye, lung, cardiovascular and immune system diseases, and even induce cancer or death. The development of real-time, rapid, and accurate monitoring technology for sub-ppm NO2 gas is of great practical significance to protecting the quality of the ecological environment and human health.

[0004] Metal oxide semiconductors (MOS) have the advantages of low cost, simple fabrication, and good compatibility with microelectronic processes, providing a promising platform for chemiresistive gas sensors. MOS gas sensors based on SnO2, ZnO, Fe2O3, Co3O4, In2O3, WO3, NiO, etc. have been widely used in various gas detections in the environmental field. Among these MOS, tin oxide (SnO2) is a typical n-type wide bandgap semiconductor, which has attracted special attention due to its high conductivity and excellent chemical and thermal stability. Due to these properties, many types of commercial devices based on SnO2 have been manufactured and are widely used to detect NO2 harmful gases. At the same time, indium oxide (In2O3), as a typical MOS, is widely used in the detection of NO2 gas due to its excellent photoelectrochemical stability.

[0005] However, single SnO2 materials, such as Ov-SnO2 synthesized by plasma spraying technology by Wang et al. [1] The material test of NO2 gas needs to work at a high temperature of 100°C, and the response recovery time is 65 / 151 s. There are still problems such as high working temperature and long response recovery time. At the same time, simple SnO2 composite materials also have the same problems. For example, Bhangare et al. synthesized SnO2 / RGO by hydrothermal method. [2]Composite materials, working temperature is 200℃, response recovery time is 10 / 20 s. In2O3 has good photocatalytic properties. For example, Cai et al. used a simple electrospinning method to synthesize a series of In2O3 [3] Nanoparticle-modified porous gold nanoparticles (NPs) are embedded in ZnO nanofibers (NFs). Under UV light irradiation, the sensor's response to 5 ppm NO2 gas can reach 95.15. It is not difficult to find that among these methods, photoactivation has attracted increasing attention as a reliable sensitization strategy that can significantly improve the conductivity of the sensor. The heterostructure under light irradiation can effectively separate the photoexcited electron-hole pairs, thereby significantly improving the sensing performance under light activation.

[0006] References: [1] Wang T, Xing Q, Zhai R, et al. Defect Engineering forSnO2Improves NO2Gas Sensitivity by Plasma Spraying[J]. ACS sensors, 2024. [2] Bhangare B, Ramgir NS, Jagtap S, et al. XPS and Kelvin probestudies of SnO2 / RGO nanohybrids based NO2sensors[J]. Applied Surface Science, 2019, 487: 918-929. [3] Cai Z, Park J, Park S. Room temperature selective detection ofNO2using Au-decorated In2O3nanoparticles embedded in porous ZnO nanofibers[J]. Journal of Alloys and Compounds, 2023, 965: 171352. Summary of the invention In view of the shortcomings of the existing SnO2-based NO2 gas sensor, such as the operating temperature is too high and the response recovery time is too long, the present invention is designed to provide a NO2 gas sensor material that can work in a room temperature environment. In order to achieve the above technical objectives, the present invention provides the following technical solutions: In the first aspect, a SnO2@In2O3 visible light excited gas sensitive material is provided, wherein the gas sensitive material is a eutectic material of SnO2 and In2O3, wherein the atomic ratio of In:Sn is 2-6:10, the eutectic molecular size is 2-4 μm, and the XRD diffraction pattern thereof comprises 2 θ The X-ray diffraction peaks are at 26.60±0.1, 30.60±0.1, 33.90±0.1, 35.40±0.1, 51.04±0.1, and 51.80±0.1.

[0007] Among the above-mentioned gas-sensitive materials, SnO2 is a hollow nanomaterial, and In2O3 is a hollow micron material, and the two form a eutectic by grinding and heating. According to high-resolution transmission electron microscopy and EDS spectrum detection, the hollow gas-sensitive material formed by the composite of SnO2 and In2O3 has a larger specific surface area and more oxygen defects, which will adsorb more gas molecules to participate in the reaction. At the same time, after adding light, a large number of photogenerated electrons and photogenerated holes will be formed on the SnO2@In2O3 visible light-excited gas-sensitive material to participate in the reaction. The heterogeneous structure of the SnO2@In2O3 visible light-excited gas-sensitive material will promote the effective separation of photogenerated electron-hole pairs, thereby improving the electron migration efficiency and increasing the carrier concentration, promoting the adsorption and desorption process with NO2, thereby achieving high-sensitivity and high-stability detection under room temperature conditions.

[0008] In a second aspect, a method for preparing the SnO2@In2O3 visible light excited gas sensitive material described in the first aspect is provided, the steps are as follows: The SnO2 hollow nanospheres and In2O3 hollow microtubes are fully mixed at an In:Sn atomic ratio of 20-60at%, and heated at 380-420°C for 1.5-2.5h to obtain the obtained product.

[0009] In the above preparation method, the In:Sn atomic ratio has a significant effect on the nitrogen dioxide response performance of the gas-sensitive material. It has been verified that when the In:Sn atomic ratio is 20~60at%, the above-mentioned gas-sensitive material can achieve rapid response under room temperature and light conditions, and the recovery time can be shortened to less than 30s. In the preferred scheme, the In:Sn atomic ratio is 35~50at%, and in a further scheme, it is 35~45at%. Feasible examples are 38at%, 39at%, 40at%, and 41at%.

[0010] In addition, in order to ensure the uniform mixing of SnO2 hollow nanospheres and In2O3 hollow microtubes, the above-mentioned uniform mixing process is preferably performed by grinding, such as mortar grinding, and the grinding time is 50 to 60 minutes.

[0011] The above heating process should adopt closed heating, such as muffle furnace heating.

[0012] In addition, the above-mentioned SnO2 hollow nanospheres and In2O3 hollow microtubes were synthesized separately by a one-step hydrothermal method, and the preparation of the two materials was not in any particular order: Among them, the preparation steps of SnO2 hollow nanospheres are as follows: dissolve SnCl4•5H2O in ethanol solution, add acid to adjust the pH of the reaction system to 5.0-6.0, transfer the above solution to a reactor, heat at 170-190°C for 18-22 hours, wash and dry the product to obtain the SnO2 hollow nanospheres; the above washing process can be carried out alternately with water and anhydrous ethanol and then transferred to a 40-60°C vacuum drying oven for drying for 10-14 hours.

[0013] Furthermore, the pH of the reaction system is preferably adjusted with a concentrated hydrochloric acid solution. After the acid is added, the solution system is subjected to ultrasonic treatment to fully disperse it. The ultrasonic treatment time may be 40-60 minutes.

[0014] Furthermore, in the above reaction, the dosage ratio of SnCl4•5H2O to the ethanol solution is 0.360~0.560g:75~80mL, and the dosage ratio of water to ethanol in the ethanol solution is 70:5~10.

[0015] The preparation steps of In2O3 hollow microtubes are as follows: In(NO3)3•xH2O and 3,5-di-tert-butylcatechol (H2BDC) are added to N,N-dimethylformamide (DMF) and fully dispersed to obtain a solution, the solution is transferred to a reactor, and maintained at 100~120°C for 3.5~5 hours. After washing and drying the reaction product, it is heated at 420~470°C for 4~6 hours to obtain In2O3 hollow microtubes.

[0016] Further, the dosage ratio of In(NO3)3•xH2O, H2BDC and DMF is 0.150~0.280g: 0.451~0.581g:60~80mL.

[0017] In a third aspect, the application of the SnO2@In2O3 visible light excited gas sensitive material described in the first aspect in the field of preparing nitrogen dioxide gas sensors is provided.

[0018] Relying on the sensitive detection effect of the above-mentioned gas-sensitive materials, those skilled in the art may anticipate using the above-mentioned gas-sensitive materials for preparing nitrogen dioxide sensors. Feasible implementation methods include using the above-mentioned gas-sensitive materials as resistive films of interdigitated electrodes, or using the above-mentioned gas-sensitive materials for preparing sensor chips, etc.

[0019] In a fourth aspect, a nitrogen dioxide detection sensor chip is provided, characterized in that the chip coating contains the gas-sensitive material described in the first aspect.

[0020] In one embodiment provided by the present invention, the preparation method of the above-mentioned sensor chip is as follows: the gas-sensitive material described in the first aspect is added to isopropanol to dissolve it ultrasonically, and then coated on the chip and dried naturally; wherein the dosage ratio of the gas-sensitive material to isopropanol is 8~12 mg:55~65μL.

[0021] Compared with the prior art, the present invention has the following beneficial effects: In order to achieve the above technical objectives, the present invention is designed to provide a SnO2@In2O3 visible light excited gas sensitive material, by synthesizing SnO2 hollow nanospheres and MOF derived In2O3 hollow microtubes respectively by a one-step hydrothermal method, and finally synthesizing SnO2@In2O3 visible light excited gas sensitive material by heating after mixing in a certain proportion. According to the test, under room temperature conditions, the best performance response value of the SnO2@In2O3 visible light excited gas sensitive material is 324.67, and the response recovery time is 21s / 18s, which is 5.5 times higher than the response value of the pure phase SnO2 material. At the same time, the response recovery time of the material before adding light is shortened by more than 5 times, and the detection limit reaches 100ppb, and the material has good repeatability for NO2 detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0023] Figure 1 This is the process flow chart for the preparation of SnO2@In2O3 visible light excited gas sensitive materials; Figure 2 The morphology characterization results of SI-NST-x at% described in Example 1; in, Figure 2 (a) XRD patterns of SI-NST-x at% (x is 0, 20, 40 and 60, respectively); Figure 2 (b) Transmission electron microscope image of SI-NST-40 at% and EDS spectra of Sn, In and O elements; Figure 3 The dynamic resistance response recovery curve of SI-NST-40 at%-light to 10 ppm nitrogen dioxide described in Example 1; Figure 4 is the repeatability curve of SI-NST-40 at%-light for 10 ppm nitrogen dioxide for 5 cycles described in Example 1; Figure 5The dynamic resistance response recovery curve of SI-NST-40 at%-light to 0.1-10 ppm nitrogen dioxide described in Example 1; Figure 6 The dynamic resistance response recovery curve of SI-NST-40 at% to 10 ppm nitrogen dioxide described in Example 1; Figure 7 The dynamic resistance response recovery curve of SI-NST-0 at%-light to 10 ppm nitrogen dioxide described in Example 1; Figure 8 The dynamic resistance response recovery curve of SI-NST-20 at%-light to 10 ppm nitrogen dioxide described in Example 1; Fig. 9 This is the dynamic resistance response recovery curve of SI-NST-60 at%-light described in Example 1 to 10 ppm nitrogen dioxide. DETAILED DESCRIPTION

[0024] It should be noted that the following detailed descriptions are all illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0025] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0026] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0027] Example 1 In this embodiment, a method for preparing SnO2@In2O3 visible light excited gas sensitive material is provided, and the steps are as follows: (1) Synthesis of SnO2 hollow nanospheres: 0.460 g SnCl4•5H2O was dissolved in a mixture of deionized water and ethanol in a ratio of deionized water: ethanol (70 mL: 7 mL), 36.5%~38.0% concentrated hydrochloric acid was added to adjust the pH to 5.0-6.0, and the solution was ultrasonically treated for 40-60 minutes to obtain a uniformly mixed solution. Subsequently, the mixed solution was transferred to a stainless steel high-pressure container lined with polytetrafluoroethylene (volume 80 mL) and kept at 180°C for 20 hours. The solid part was retained by centrifugation, and after alternately washing with deionized water and ethanol, it was vacuum dried at 40-60°C for 12 hours to obtain SnO2 hollow nanospheres.

[0028] (2) Synthesis of MOF-derived In2O3 hollow microtubes: 0.180 g In(NO3)3•xH2O and 0.481 g H2BDC (3,5-di-tert-butylcatechol) were added to 60 mL DMF (N,N-dimethylformamide) and stirred, and then the solution was ultrasonically treated for 30 minutes to obtain a mixed solution. Subsequently, the mixed solution was transferred to a stainless steel high-pressure container lined with polytetrafluoroethylene (volume 80 mL) and kept at 100°C for 4 hours. The solid part was retained by centrifugation, washed, vacuum dried at 40-60°C for 12 hours, and transferred to a tube furnace and heated at 450°C for 4 hours to obtain In2O3 hollow microtubes.

[0029] (3) Synthesis of SnO2@In2O3 visible light excited gas sensitive material: The SnO2 hollow nanospheres and In2O3 hollow microtubes synthesized above were mixed with In:Sn atomic ratios of 0 at%, 20 at%, 40 at%, and 60 at%, respectively, and ground in a mortar for 60 min. After heating in a muffle furnace at 400 °C for 2 h, the SnO2@In2O3 visible light excited gas sensitive material was obtained, denoted as SI-NST-xat% (x was 0, 20, 40, and 60, respectively).

[0030] Material structure characterization: The morphological characterization results of the above SI-NST-x at% (x is 0, 20, 40 and 60 respectively) are shown in Figure 2 , Figure 2 (a) is the XRD spectrum. It can be seen from the figure that the diffraction peaks (101), (110), (211) corresponding to SnO2 and (222), (400), (440) corresponding to In2O3 appear without any impurity peaks. The SnO2@In2O3 visible light excitation gas sensitive material was successfully synthesized. Figure 2 (b) is the transmission electron microscope image of SI-NST-40 at% and the EDS spectra of Sn, In and O elements. It can be seen that SnO2 is in the shape of hollow nanospheres, In2O3 is in the shape of hollow microtubes, and the elements are evenly distributed.

[0031] Test method: SnO2@In2O3 visible light excited gas sensitive material was prepared in the ratio of 10 mg:60 μL isopropanol, ultrasonicated for 15 min, 10 μL was dropped on the chip (alumina ceramic interdigitated gold electrode with an electrode spacing of 0.02 mm and a specification of 13.4 mm*7 mm) and dried naturally, and then the gas sensitive test was performed after drying.

[0032] First, connect the coated chip with a wire, place it in a sealed air chamber filled with clean air, and connect it to a digital source meter (KEITHLEY 2400) through a wire. Set the working voltage to 2V. At this time, the sensor is in contact with the clean air in the air chamber. After stabilization, add an LED light source outside the air chamber. The external light source device is MC-LED-VIS, with a wavelength range of 450 nm-460 nm, and the working current is set to 0.05 A. After adding light, the stabilized baseline resistance measured by the digital source meter is defined as (R air Then, under the condition of adding light, the gas sensor is transferred to a closed gas chamber with a certain concentration of NO2. The stable resistance obtained at this time is recorded as (R gas )Finally, the response value S = R gas / R air Place the gas sensor back into the sealed chamber filled with clean air, and the resistance returns to the baseline resistance (R air ) to complete the test. By mixing clean air with different volumes of standard concentration target gas, different concentrations of target gas can be obtained. Different concentrations of target gas can be calculated by formula (1): C = Vs×Cs / V , (1) C : Target gas concentration in parts per million (ppm).

[0033] Vs : The standard volume of gas injected into the chamber, measured in volume units.

[0034] Cs : Concentration of standard gas (100 ppm standard gas mixed with clean air, 78% N2 and 22% O2).

[0035] V :The volume of the gas chamber, measured in volume units (160 mL).

[0036] The above static test was conducted at a temperature of 24.8°C with and without light, respectively. The light-added experimental group was denoted as SI-NST-x at%-light. Figure 3-5The test result of SI-NST-40 at% under light condition is recorded as SI-NST-40 at%-light. Figure 6 The results of SI-NST-40 at% testing without light are denoted as SI-NST-40 at%. Figure 7-9 These are the test results of SI-NST-x at% (x is 0, 20 and 60 respectively) under light addition conditions, recorded as SI-NST-x at%-light (x is 0, 20 and 60 respectively).

[0037] Table 1 Response value and response recovery time of SI-NST-x to NO2 By comparing the above Figure 3 , Figure 7 , Figure 8 , Fig. 9 The results show that SI-NST-40 at% has the shortest dynamic resistance response recovery time to 10ppm nitrogen dioxide and is the most sensitive. Figure 4 From the results, the sensitive response ability of SI-NST-40 at% also has good stability, and has basically consistent performance in multiple cycles; Figure 5 The SI-NST-40 at% response to different concentrations of nitrogen dioxide is shown. It can be seen that the SI-NST-40 at% response varies linearly with the concentration of nitrogen dioxide, and the lowest concentration of nitrogen dioxide can be detected at 0.1 ppm. Figure 6 ), the response of SI-NST-40 at% to 10 ppm nitrogen dioxide showed a significant delay, indicating that the above materials require visible light excitation.

[0038] In addition, the above-mentioned SI-NST-60 at% also has a good response effect to nitrogen dioxide under light-added conditions, and the response time to 10 ppm NO2 gas at room temperature is 18s and 30s, as a response material at room temperature. Based on the above test results, this embodiment can reasonably infer that SI-NST-x at%, x is in the range of 30~60at%, and is expected to achieve good detection sensitivity at room temperature.

[0039] Example 2 In this embodiment, another method for preparing SnO2@In2O3 visible light excited gas sensitive material is provided, and the steps are as follows: (1) Synthesis of SnO2 hollow nanospheres: 0.460 g SnCl4•5H2O was dissolved in a mixture of deionized water and ethanol in a ratio of deionized water: ethanol (70 mL: 7 mL), 36.5%~38.0% concentrated hydrochloric acid was added to adjust the pH to 5.0-6.0, and the solution was ultrasonically treated for 40-60 minutes to obtain a uniformly mixed solution. Subsequently, the mixed solution was transferred to a stainless steel high-pressure container lined with polytetrafluoroethylene (volume 80 mL) and kept at 180°C for 20 hours. After centrifugation, it was alternately washed with deionized water and ethanol, and then vacuum dried at 40-60°C for 12 hours to obtain SnO2 hollow nanospheres.

[0040] (2) Synthesis of MOF-derived In2O3 hollow microtubes: 0.180 g In(NO3)3•xH2O and 0.481 g H2BDC (3,5-di-tert-butylcatechol) were added to 60 mL DMF (N,N-dimethylformamide) and stirred. The solution was ultrasonically treated for 30 minutes to obtain a uniformly mixed solution. Subsequently, the mixed solution was transferred to a stainless steel high-pressure container (volume 80 mL) lined with polytetrafluoroethylene and kept at 100°C for 4 hours. After centrifugal washing, the In2O3 hollow microtubes were obtained after vacuum drying at 40-60°C for 12 hours and heating at 450°C in a tube furnace for 4 hours.

[0041] (3) Synthesis of SnO2@In2O3 visible light excited gas sensitive material: The SnO2 hollow nanospheres and In2O3 hollow microtubes synthesized above were mixed at an In:Sn atomic ratio of 40 at%, ground in a mortar for 60 min, and then heated in a muffle furnace at 400 °C for 2 h to obtain SnO2@In2O3 visible light excited gas sensitive material.

[0042] Example 3 In this embodiment, another method for preparing SnO2@In2O3 visible light excited gas sensitive material is provided, and the steps are as follows: (1) Synthesis of SnO2 hollow nanospheres: 0.560 g SnCl4•5H2O was dissolved in a mixture of deionized water and ethanol in a ratio of deionized water: ethanol (70 mL: 10 mL). 36.5%~38.0% concentrated hydrochloric acid was added to adjust the pH to 5.0-6.0, and the solution was ultrasonically treated for 40-60 minutes to obtain a uniformly mixed solution. Subsequently, the mixed solution was transferred to a stainless steel high-pressure container lined with polytetrafluoroethylene (volume 80 mL) and kept at 190°C for 18 hours. After centrifugation, it was alternately washed with deionized water and ethanol, and then vacuum dried at 40-60°C for 10 hours to obtain SnO2 hollow nanospheres.

[0043] (2) Synthesis of MOF-derived In2O3 hollow microtubes: 0.280 g In(NO3)3•xH2O and 0.581 g H2BDC (3,5-di-tert-butylcatechol) were added to 80 mL DMF (N,N-dimethylformamide) solution and stirred. The solution was then ultrasonically treated for 40 minutes to obtain a uniformly mixed solution. Subsequently, the mixed solution was transferred to a stainless steel high-pressure container (volume 80 mL) lined with polytetrafluoroethylene and kept at 120°C for 3.5 hours. After centrifugal washing, the In2O3 hollow microtubes were obtained after vacuum drying at 40-60°C for 13 hours and heating at 420°C in a tube furnace for 5 hours.

[0044] (3) Synthesis of SnO2@In2O3 visible light excited gas sensitive material: The SnO2 hollow nanospheres and In2O3 hollow microtubes synthesized above were mixed at an In:Sn atomic ratio of 50 at%, ground in a mortar for 50 min, and then heated in a muffle furnace at 420 °C for 1.5 h to obtain SnO2@In2O3 visible light excited gas sensitive material.

[0045] Example 4 In this embodiment, another method for preparing SnO2@In2O3 visible light excited gas sensitive material is provided, and the steps are as follows: (1) Synthesis of SnO2 hollow nanospheres: 0.360 g SnCl4•5H2O was dissolved in a mixture of deionized water and ethanol in a ratio of deionized water: ethanol (70 mL: 5 mL). 36.5%~38.0% concentrated hydrochloric acid was added to adjust the pH to 5.0-6.0, and the solution was ultrasonically treated for 40-60 minutes to obtain a uniformly mixed solution. Subsequently, the mixed solution was transferred to a stainless steel high-pressure container lined with polytetrafluoroethylene (volume 80 mL) and kept at 170°C for 22 hours. After centrifugation, it was alternately washed with deionized water and ethanol, and then vacuum dried at 40-60°C for 14 hours to obtain SnO2 hollow nanospheres.

[0046] (2) Synthesis of MOF-derived In2O3 hollow microtubes: 0.150 g In(NO3)3•xH2O and 0.451 g H2BDC (3,5-di-tert-butylcatechol) were added to 50 mL DMF (N,N-dimethylformamide) solution and stirred. The solution was then ultrasonically treated for 25 minutes to obtain a uniformly mixed solution. Subsequently, the mixed solution was transferred to a stainless steel high-pressure container (volume 80 mL) lined with polytetrafluoroethylene and kept at 105°C for 5 hours. After centrifugal washing, the In2O3 hollow microtubes were obtained after vacuum drying at 40-60°C for 10 hours and heating at 470°C in a tube furnace for 6 hours.

[0047] (3) Synthesis of SnO2@In2O3 visible light excited gas sensitive material: The SnO2 hollow nanospheres and In2O3 hollow microtubes synthesized above were mixed at an In:Sn atomic ratio of 30 at%, ground in a mortar for 55 min, and then heated in a muffle furnace at 380 °C for 2.5 h to obtain SnO2@In2O3 visible light excited gas sensitive material.

[0048] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A SnO2@In2O3 visible light excited gas sensitive material, characterized in that: The gas-sensitive material is a eutectic material of SnO2 and In2O3, wherein the atomic ratio of In:Sn is 2-6:10, the particle size of the eutectic molecule is 2-4 μm, and its XRD diffraction spectrum contains 2 θ The X-ray diffraction peaks are at 26.60±0.1, 30.60±0.1, 33.90±0.1, 35.40±0.1, 51.04±0.1, and 51.80±0.

1.

2. The method for preparing the SnO2@In2O3 visible light excited gas sensitive material according to claim 1, characterized in that: Here are the steps: The SnO2 hollow nanospheres and In2O3 hollow microtubes are ground and mixed according to the In:Sn atomic ratio of 20-60at%, and heated at 380-420℃ for 1.5-2.5h to obtain the product.

3. The preparation method according to claim 2, characterized in that: The In:Sn atomic ratio is 35-50 at %, preferably 35-45 at %, specifically 38 at %, 39 at %, 40 at % or 41 at %.

4. The preparation method according to claim 2, characterized in that: The grinding time is 50 to 60 minutes.

5. The preparation method according to claim 2, characterized in that: The preparation steps of the SnO2 hollow nanospheres are as follows: dissolving SnCl4•5H2O in an ethanol solution, adding acid to adjust the pH of the reaction system to 5.0-6.0, transferring the above solution to a reactor, heating at 170-190°C for 18-22 hours, washing and drying the product to obtain the SnO2 hollow nanospheres; the washing process uses water and anhydrous ethanol for alternating washing and then transfers to a 40-60°C vacuum drying oven for drying for 10-14 hours.

6. The preparation method according to claim 5, characterized in that: The pH of the reaction system is adjusted to a concentrated hydrochloric acid solution, and after adding the acid, the solution system is ultrasonically treated to fully disperse it, and the ultrasonic time is 40-60 minutes; Alternatively, the dosage ratio of SnCl4•5H2O to the ethanol solution is 0.360-0.560 g:75-80 mL, and the dosage ratio of water to ethanol in the ethanol solution is 70:5-10.

7. The preparation method according to claim 2, characterized in that: The preparation steps of the In2O3 hollow microtubes are as follows: In(NO3)3•xH2O and H2BDC are added to DMF and fully dispersed to obtain a solution, the solution is transferred to a reactor, and maintained at 100-120°C for 3.5-5 hours, and the reaction product is washed and dried and heated at 420-470°C for 4-6 hours to obtain In2O3 hollow microtubes.

8. The preparation method according to claim 7, characterized in that: The dosage ratio of In(NO3)3•xH2O, H2BDC and DMF is 0.150~0.280g:0.451~0.581g:60~80mL.

9. Application of the SnO2@In2O3 visible light excited gas sensitive material according to claim 1 in the preparation of nitrogen dioxide gas sensors.

10. A nitrogen dioxide detection sensor chip, characterized in that: The chip coating contains the gas-sensitive material according to claim 1; The preparation method of the sensor chip is as follows: adding the gas-sensitive material of claim 1 into isopropanol to dissolve it by ultrasonication, coating it on the chip and drying it naturally; wherein the dosage ratio of the gas-sensitive material to isopropanol is 8-12 mg:55-65 μL.